2016
DOI: 10.1136/bmjopen-2015-010084
|View full text |Cite
|
Sign up to set email alerts
|

Realist synthesis of educational interventions to improve nutrition care competencies and delivery by doctors and other healthcare professionals

Abstract: ObjectiveTo determine what, how, for whom, why, and in what circumstances educational interventions improve the delivery of nutrition care by doctors and other healthcare professionals work.DesignRealist synthesis following a published protocol and reported following Realist and Meta-narrative Evidence Synthesis: Evolving Standards (RAMESES) guidelines. A multidisciplinary team searched MEDLINE, CINAHL, ERIC, EMBASE, PsyINFO, Sociological Abstracts, Web of Science, Google Scholar and Science Direct for publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
77
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 82 publications
9
77
0
4
Order By: Relevance
“…The results of the current review are consistent with the findings of others (8,10,16,18) in this area in that there is a lack of evidence of either effectiveness or ineffectiveness of staff nutrition training interventions. In a review assessing the impact of interventions to indirectly support food and drink intake in people with dementia, Abdelhamid et al (12) reported that the training interventions were too small and/or short-term for any definitive conclusions to be drawn regarding effectiveness.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the current review are consistent with the findings of others (8,10,16,18) in this area in that there is a lack of evidence of either effectiveness or ineffectiveness of staff nutrition training interventions. In a review assessing the impact of interventions to indirectly support food and drink intake in people with dementia, Abdelhamid et al (12) reported that the training interventions were too small and/or short-term for any definitive conclusions to be drawn regarding effectiveness.…”
Section: Discussionsupporting
confidence: 88%
“…Malnourished individuals experience longer hospital stays (1,2) and are more likely to be institutionalized (3)(4)(5), and as a result, the costs associated with malnutrition have been estimated as £14 billion, V120 billion, and $432 billion each year in the United Kingdom, Europe, and the United States, respectively. Although the need to improve nutritional care has long been recognized and clinical guidance for the detection and management of malnutrition exists (6), nutritional care is often inadequate (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectures may be a good way of introducing new concepts to students but lectures alone might not enhance self-efficacy as its opportunities for practical and clinical experiences are limited [48]. In identifying teaching and learning methods that could promote self-efficacy as well as attitudes in nutrition care, Mogre et al [34] found the following to be important: role modelling by practicing physicians [49], role playing using either simulated or real patients [50][51][52][53], encouraging clinical bedside nutritional teaching [48], demonstrations and hands on practice sessions [49][50][51][52][54][55][56], viewing and discussion of videos and Web-based cases [51,57].…”
Section: Discussionmentioning
confidence: 99%
“…In such settings, it would be most imperative to conduct an evaluation of the situation of nutrition education, the confidence, knowledge and attitudes of future medical doctors as a necessary step towards empowering them to be able to provide nutrition care to prevent and reduce the burden of diet-related diseases [27][28][29][30][31][32][33]. The findings of a recent realist review of educational interventions to improve nutrition care competencies and delivery by doctors and other healthcare professionals highlighted the importance of undertaking a needs assessment in this direction [34].…”
Section: Introductionmentioning
confidence: 99%